2003
DOI: 10.1002/app.12679
|View full text |Cite
|
Sign up to set email alerts
|

Modification of acrylonitrile–butadiene–styrene terpolymer by grafting with maleic anhydride in the melt. I. Preparation and characterization

Abstract: ABSTRACT:The graft copolymerization of maleic anhydride (MAH) onto acrylonitrile-butadiene-styrene terpolymer (ABS) was carried out with dicumyl peroxide (DCP) and benzoyl peroxide (BPO) as the binary initiators and with styrene as the comonomer in the molten state. IR spectra confirmed that MAH was successfully grafted onto the ABS backbone. A reaction mechanism was proposed: the grafting most likely took place through the addition of MAH radicals to the double bond of the butadiene region of ABS. Influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…The impact strength of ABS-g-GMA/St decreased as the initiator concentration increased, as shown in Figure 8 , which may be explained by the grafting reaction occurring most likely in the butadiene region of ABS, and thus the contents of the butadiene region (rubber region) are decreased with increased initiator concentration, which is also reported in Rao et al ' s work [22] and Qi et al ' s work [23] . …”
Section: Effect Of Initiator Concentrationsupporting
confidence: 65%
“…The impact strength of ABS-g-GMA/St decreased as the initiator concentration increased, as shown in Figure 8 , which may be explained by the grafting reaction occurring most likely in the butadiene region of ABS, and thus the contents of the butadiene region (rubber region) are decreased with increased initiator concentration, which is also reported in Rao et al ' s work [22] and Qi et al ' s work [23] . …”
Section: Effect Of Initiator Concentrationsupporting
confidence: 65%
“…As expected, with MA increasing from 1.5 to 6 phABS, the GD increases significantly up to 2.43% (B1 to B4). Other researchers have reported the same results on the effects of the various initiators and MA concentrations on the grafting process [19, 20]. To investigate the importance of the grafting reaction on the blending performance, compatibilized blends of W‐PET containing two types of ABS‐ g ‐MA (B2 and B4) were compared with uncompatibilized ones containing virgin ABS.…”
Section: Resultsmentioning
confidence: 85%
“…The mixed solution was back‐titrated with HCl solution (0.1 mol/L), and methyl red was used as an indicator. Finally, the amount of grafted MA as a percentage of ABS‐ g ‐MA was calculated from the following equation: where V 0 is the volume of HCl consumed by pure ABS as a reference (mL), V 1 is the volume of HCl consumed by grafted ABS (mL), C is the molar concentration of HCl (mol/L), M is the molecular weight of maleic anhydride, and W is the weight of the sample (g) [19].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, 33 we also found that St, as the electron-donating compound because there exists floating electron cloud for its p-p conjugation, could effectively decrease the GC of the grafting copolymers. To investigate the effects of St on the HDPE-g-MAH copolymer, binary systems of St, and MAH with various compositions were used.…”
Section: Effect Of the Comonomermentioning
confidence: 94%